Linguistic Etiquette In Communication - Carla Maretha; Gali Alrajafi; Yulia Wahyuningsih (Universitas Muhammadiyah Lampung, 2021)
There are three factors influence children in their daily communications. First is social distance, this factor shows the discrepancy of delivering their aims to older people and it affects impoliteness in communication, for instance, using Javanese word kowe to their parents. Then, in social interaction, the children assert their statement by adding some animal and impolite words to their friends, and they think it as trend in nowadays communication. The second factor is social power consists of four aspects; interlocutors’ position, age, gender, and language impairment. This factor is much influenced by education background and understanding of religion. The third is degree of imposition which explains children’s way of uttering their will. It shows that when children speak to friends or parents, they do not care their words and intonation.